Legal Protection for Consumers in the Parate Execution of Fiduciary Guarantee Objects - Davina Tasya Kirana Pakaya (Fox Justi : Jurnal Ilmu Hukum, 2025)
This research addresses the problem of inadequate legal protection for consumers in the implementation of parate execution of fiduciary collateral objects. The study aims to examine regulations, transparency, and fair treatment of consumers within this context. Employing normative legal research through the analysis of legal literature and secondary data, the study explores the legal relationship between debtors and creditors in Consumer Finance Companies, highlighting the principle of freedom of contract under Article 1338 paragraph 1 of the Indonesian Civil Code. Findings indicate that parate execution must comply with consumer protection principles concerning security, safety, and legal certainty, as mandated by Law No. 8 of 1999 on Consumer Protection. The research concludes that additional protections, such as requiring debtor agreement or court approval for execution, are necessary, alongside recommendations for legal education, enhanced government oversight, and stricter adherence to the principle of prudence in fiduciary collateral execution.